SUCCESSFUL MANAGEMENT OF SACRAL POSTHERPETIC NEURALGIA WITH GANGLION IMPAR BLOCK - A CASE REPORT - S, PARTHASARATHY; BATCHA S, ANWAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Postherpetic neuralgia (PHN) is one of the most common and important complications of severe varicella-zoster infection, especially occurring in 20% of the elderly patients. A 59-year-old female presented with pain in the right sacral region for the past 3 months. The pain was preceded by herpes zoster. She was diagnosed as a case of Sacral PHN. We administered paramedian approach of ganglion impar block with 10 ml of 0.25% bupivacaine with 8 mg dexamethasone which resulted in immediate adequate pain relief. On follow-up after 8 weeks, the pain score continued to be less with 3/10. No complications were encountered. There was no sensory loss. We conclude that ganglion impar block with a combination of local anesthetic and steroid is a viable treatment option for sacral PHN.